Local gene expression changes after UV-irradiation of human skin - Weinkauf, Benjamin; Rukwied, Roman; Schmelz, Martin (PLOS ONE, 2012)
UV-irradiation is a well-known translational pain model inducing local inflammation and primary hyperalgesia. The mediators and receptor proteins specifically contributing to mechanical or heat hyperalgesia are still unclear. Therefore, we irradiated buttock skin of humans (n = 16) with 5-fold MED of UV-C and assessed the time course of hyperalgesia and axon reflex erythema. In parallel, we took skin biopsies at 3, 6 and 24 h after UVC irradiation and assessed gene expression levels (RT-PCR ) of neurotrophins (e.g. NGF, BDNF, GDNF), ion channels (e.g. NaV1.7, TRPV1), inflammatory mediators (e.g. CCL-2, CCL-3) and enzymes (e.g. PGES, COX2). Hyperalgesia to mechanical impact (12 m/s) and heat (48°C) stimuli was significant at 6 h (p<0.05 and p<0.01) and 24 h (p<0.005 and p<0.01) after irradiation. Axon reflex erythema upon mechanical and thermal stimuli was significantly increased 3 h after irradiation and particularly strong at 6 h. A significant modulation of 9 genes was found post UV-C irradiation, including NGF (3, 6, 24 h), TrkA (6, 24 h), artemin, bradykinin-1 receptor, COX-2, CCL-2 and CCL-3 (3 and 6 h each). A significant down-regulation was observed for TRPV1 and iNOS (6, 24 h). Individual one-to-one correlation analysis of hyperalgesia and gene expression revealed that changes of Nav1.7 (SCN9A) mRNA levels at 6 and 24 h correlated to the intensity of mechanical hyperalgesia recorded at 24 h post UV-irradiation (Pearson r: 0.57, p<0.04 and r: 0.82, p<0.001). Expression of COX-2 and mPGES at 6 h correlated to the intensity of heat-induced erythema 24 h post UV (r: 0.57, p<0.05 for COX-2 and r: 0.83, p<0.001 for PGES). The individual correlation analyses of functional readouts (erythema and pain response) with local expression changes provided evidence for a potential role of Nav1.7 in mechanical hyperalgesia.